2011
DOI: 10.1111/j.1600-0560.2011.01760.x
|View full text |Cite
|
Sign up to set email alerts
|

Erythema elevatum diutinum - a chronic leukocytoclastic vasculitis microscopically indistinguishable from granuloma faciale?

Abstract: The histopathology of GF and EED is very similar and overlapping. The presence of a Grenz zone and patterned fibrosis does not distinguish the two diseases. However, granulomatous nodules are only seen in EED, and a predominance of eosinophils in the infiltrate favors a diagnosis of GF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 42 publications
0
21
0
7
Order By: Relevance
“…However, it is known that these changes present in a very similar pattern in two entities, not being sufficient for differentiation. 4 All the patients in this study had facial lesions. Most samples entailed a typical, perivascular, inflammatory pattern.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…However, it is known that these changes present in a very similar pattern in two entities, not being sufficient for differentiation. 4 All the patients in this study had facial lesions. Most samples entailed a typical, perivascular, inflammatory pattern.…”
Section: Discussionmentioning
confidence: 90%
“…15 Immunohistochemical analysis of samples from this study revealed a superiority of CD8+ T cells compared with CD4+ T lymphocytes, differing from the current literature. 3,4,5,6,7,12 …”
Section: Discussionmentioning
confidence: 99%
“…It is seen in granuloma faciale, erythema elevatum diutinum, eosinophilic angiocentric fibrosis, inflammatory pseudotumors, and IgG4-related sclerosing diseases. [4][5][6][7][8] These conditions share a chronic slowly progressive course, resistance to medical therapy, and a dense fibroid texture. LCFV is thought to be caused by a poor clearance of antigen, but there are only a small number of cases in which a possible antigenic stimulus has been identified.…”
Section: Discussionmentioning
confidence: 99%
“…Although the etiology of the disease is unknown, it is related to the deposit of immune complexes on the wall of post-capillary venules, activation of the complement cascade, and neutrophil chemotaxis, releasing lisoenzimes, collagenase, myeloperoxidase and hydrolases that induce fibrin deposits in and around the capillaries and venules. 5,6 The lesions consist mainly of persistent and symmetrical erythematous papules, plaques and nodules, mainly located on the extensor areas of the extremities. They are initially soft and erythematous purpuric, with occasional blisters and ulcers.…”
Section: Discussionmentioning
confidence: 99%